"Dry Eye" Is the Wrong Diagnosis for Millions. Issue 9 (September 2015) - Korb, Donald R.; Blackie, Caroline A.
Abstract : ABSTRACT: The clinical perspective that dry eye is, at best, an incomplete diagnosis and the benefit of an etiology-based approach to dry eye are presented. To provide context for this perspective, the historical and current definition of dry eye is reviewed. The paradigm shift introduced by the Meibomian Gland Dysfunction (MGD) Workshop, that MGD is likely the leading cause of dry eye, is discussed in combination with the advancements in the diagnosis and treatment of MGD. To facilitate discussion on the benefit of an etiology-based approach, a retrospective observational analysis was performed on deidentified data from eligible, fully consented, refractory dry eye patients, where conventional sequelae-based dry eye treatment had failed. In this refractory population, the diagnosis of MGD, which directed treatment to evacuating gland obstructions and rehabilitating gland function, was successful. The clinical perspective that "dry eye" is the wrong diagnosis for millions is provocative. However, the MGD-first approach has the potential to revolutionize the timing of diagnosis and the choice of frontline therapy in most patients with dry eye. Additionally, the ability to screen for MGD in its earliest stages, during routine care, expands the scope of clinical practice to include early intervention. For most patients, we are no longer constrained to delay diagnosis until the tear film has decompensated and the cascade of inflammation has ensued. We do not have to wait for our patients to tell us there is a problem.